Pengaruh Gender, Pertimbangan Pasar Kerja dan Penghargaan Finansial Terhadap Motivasi Pemilihan Karir Sebagai Akuntan (Studi Kasus pada Mahasiswa Akuntansi Universitas Islam Malang) - Bhubha, Umi Kalsum; Sudaryanti, Dwiyani; Mahsuni, Abdul Wahid (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine The Influence of Gender, job Market Considerations and Financial Rewards on the Motivation for Choosing a Career as an Accountant, because these three factors in previous studies showed inconsistent results or different results. Therefore the researcher tested again to obtain more reliable results regarding various aspects that influence student motivation in choosing a profession as an accountant. The sample in this study was Accounting Students at the Islamic University of Malang class of 2019, totaling 133 respondents. Sampling using purposive sampling method. This study used a quantitative method with data collection techniques through distributing questionnaires which were measured using a Likert scale. Analysis prerequisite tests include normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique used is multiple linear regression analysis. Based on the results of the study: (1) There is a significant influence gender, job market considerations and financial rewards simultaneously on the motivation to choose a career as an accountant. (2) There is no effect of gender on the motivation to choose a career as an accountant. (3) There is a significant influence of job market considerations on the motivation for choosing a career as an accountant. (4) There is effect of financial rewards on the motivation to choose a career as an accountant.Keywords: Career selection motivation as an accountant, gender, job market considerations, financial rewards.